The Traumatic Impact of the COVID-19 Pandemic on the Psychological Distress of University Students and Professors: The Mediating Role of Self-Criticism and Experiential Avoidance - Carvalho, Catarina Santos (2021)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação